ANALYSIS OF HEALTH INSURANCE EXPENDITURE IN OUTPATIENT MANAGEMENT OF HYPERTENSION AT THE UNIVERSITY MEDICAL CENTER HO CHI MINH CITY, CAMPUS 2 (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to analyze health insurance expenditure for outpatient management of hypertension at the University Medical Center Ho Chi Minh City, Campus 2 from 2020 to 2023, and to identify factors associated with expenditure variation.Methods: A cross-sectional descriptive study was conducted using retrospective data extracted from the hospital’s health insurance payment database between 2020 and 2023. Statistical analyses were performed using Stata 16.0.Results: The average health insurance expenditure per outpatient case increased in 2021 and subsequently declined in 2023. Female patients had higher average costs than males in 2022 and 2023. Patients aged ≥ 80 years recorded the highest expenditures, as did those insured under government-funded health insurance schemes. Individuals with complications or comorbidities incurred significantly higher costs compared with those with primary hypertension alone. Differences between groups were statistically significant (p < 0.05).Conclusion: The average health insurance expenditure for outpatient hypertension management fluctuated across the study period and was influenced by demographic and clinical factors, including sex, age, insurance type, and disease condition.
Keywords: Health insurance, hypertension, outpatient care, medical cost.